« We need to […] out-innovate the world » : les tribulations de la politique de compétitivité américaine - Jean-Baptiste Velut (Revue LISA)
This article examines the changes in America’s competitiveness policy over the past three decades by focusing on three main axes: innovation policy, military-industrial policy and trade diplomacy. The objective is first to analyze the conflicts of interests, the institutional dynamics and the ideological forces that have shaped America’s ability to defend its national economic interests in the face of globalization – from renewed debates on industrial policy in the 1980s to Barack Obama’s promise to “out-educate, out-innovate and out-build the rest of the world”. From a theoretical standpoint, this article aims to analyze the resilience and mutations of America’s capitalist model during a period characterized by dramatic transformations in the global economy. In order to shed light on the shifts and continuity of American capitalism, we will seek to transcend the state-market dichotomy to reveal the complex modalities of state intervention and the interpenetration of public and private spheres.